Distribuição, alimentação e período reprodutivo de duas espécies de Tetragonopterinae (Osteichthyes) sintópicas no rio Ubatiba (Maricá, RJ) - Gomes, José Henrique Cantarino (1994)
Results related to the longitudinal distribution, reproduction and feeding of Astyanax janeiroensis Eigenmann, 1908 and Deuterodon sp. are analised , through monthly sampling in three stations of Ubatiba river (Maricá – RJ).In general, Deuterodon sp. was more abundant than A. janeiroensis. Both species were collected through all the river without showing preferences for any particular microhabitat. However for both species was observed greater incidence of bigger individuals in the upper course, whereas smaller ones were more frequent in the median and inferior course of the river. The reproductive period was estimated by monthly occurrence of mature females, the examination of gonads being limited to macroscopic observation of fixed individuals. It seems that the reproduction of Deuterodon sp. occurs in the period of November to January, whereas nothing could be concluded for A janeiroensis due to the frequency of mature females through the year. The analysis of gut content defined both species as being generalist, but with a predominance of items of allochthonous origin in the diet of A. janeiroensis. Despite the great niche overlap, competitiva interactions is perhaps being minimized by food abundance and by the lack of a specialization in the diet of A. janeiroensis and Deuterodon sp.